(3aGYdjI GSJNOGe GdJYdje GdJYGhfj ai JfejI HYV GdegGQGJ GdeYQajI dOi JdGejP eOGQS GdJQHjI GdacQjI (B/ s - (3UGdM MSf YHOGdMejO eMeOs; (3efGd eMeO eUWai (B: s; (3efi MSf GdSjO HOhi (B: s ((3GdbGgQI (B: s (3UGdM MSf YHOGdMejO eMeO (B: s, 2010)
(3JYO GdbQGAI hSjdI ef hSGFd GdJYde hGdGJUGd (B: (3MjK jJhba fLGM GdJdGejP ai GdJYdje Ydi GJbGf egGQGJ GdbQGAI hJCNP GdbQGAI ai GdeQMdI GdGHJOGFjI CgejI NGUI aYdi eOi GdfLGM ai GdbQGAI jecf QaY eSJhi GdeYGb YbdjB ef eSJhi Edi eSJhi CYdi aGdbQGAI CSGS JYdeg hCge hSjdI ddJhGab hGdJYGjT ai eLJeYg GdPj jYjT ajg hgi hSjdI dOQGSI GdehGO GdCNQi MjK Cf VYa GdJdejP ai GdbQGAI jYJHQ eTcdI cHjQI JDKQ Ydi eSJhGg GdOQGSi HGdcGed hYdi GdQZe ef CgejI GdbQGAI hefGOI GdeSFhdjf HCgejJgG EdG Cf GdOQGSGJ GdegJeI HGdbQGAI GdLgQjI dPhj GdEYGbI GdacQjI bdjdI LOBs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ hGdHMhK GdJQHhjI (B- (3bSe GdEQTGO GdfaSi h GdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJfejI HYV GdegGQGJ GdeYQajIs; (3JdGejP eOGQS GdJQHjI GdacQjIs; (3aGYdjI GSJNOGe GdJYdje GdJYGhfis